Pengembangan Sistem Service Elektronik dengan Fitur Chatbot dan Integrasi Whatsapp pada Rama Jaya Service Electronic Menggunakan Framework Laravel - Rifky Dio Arianto; Yayak Kartika Sari; Taufiq Agung Cahyono (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop a web-based electronic service system at Rama Jaya Service Electronic to improve the effectiveness of repair service management and customer communication. The study uses the Agile Kanban software development method, which allows the development process to be carried out in stages and adaptively according to user needs. Research data was obtained through observation, interviews, and literature studies. The system was developed using the Laravel framework with a MySQL database and is equipped with service management, transaction, chatbot, WhatsApp integration, and user dashboard features. The system quality was evaluated through Black Box Testing, System Usability Scale (SUS), and GTmetrix to assess aspects of system functionality, usability, and performance. The results of the study indicate that the developed system is able to support the management of electronic services more effectively and structured, accelerate the delivery of information to customers, and improve service quality. Thus, the developed web-based electronic service system can be a solution to support the digitalization of business processes at Rama Jaya Service Electronic.